2018
DOI: 10.1038/s41419-018-0392-5
|View full text |Cite
|
Sign up to set email alerts
|

The harsh microenvironment in infarcted heart accelerates transplanted bone marrow mesenchymal stem cells injury: the role of injured cardiomyocytes-derived exosomes

Abstract: Stem cell therapy can be used to repair and regenerate damaged hearts tissue; nevertheless, the low survival rate of transplanted cells limits their therapeutic efficacy. Recently, it has been proposed that exosomes regulate multiple cellular processes by mediating cell survival and communication among cells. The following study investigates whether injured cardiomyocytes-derived exosomes (cardiac exosomes) affect the survival of transplanted bone marrow mesenchymal stem cells (BMSCs) in infarcted heart. To mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(61 citation statements)
references
References 49 publications
(43 reference statements)
0
60
0
1
Order By: Relevance
“…In this study, 3~4‐week‐old male Sprague Dawley rats, weighing about 80‐100 g, were used for supplying peritoneal macrophages according to a method previously described . Cold PBS, containing 10% FBS, was injected into the rat peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, 3~4‐week‐old male Sprague Dawley rats, weighing about 80‐100 g, were used for supplying peritoneal macrophages according to a method previously described . Cold PBS, containing 10% FBS, was injected into the rat peritoneal cavity.…”
Section: Methodsmentioning
confidence: 99%
“…After left anterior descending artery ligation in the Rab27a‐knockout mouse heart, mouse bone marrow–derived MSCs were injected into the border zone of the infarct. These transplanted bone marrow–derived MSCs showed 3‐fold increased survival after 4 days . The accumulative evidence suggests that EVs, including exosomes, when produced by cells under adverse conditions, not only contribute to the disease pathology but also may be detrimental toward cardiac regenerative therapies.…”
Section: Understanding the Paracrine Effects Exerted By Exosomes Secrmentioning
confidence: 99%
“…It has recently been shown that exosomes derived from injured cardiomyocytes may impede the survival of bone marrow-derived MSCs in the infarcted heart. 11 Exosomes isolated from cultured cardiomyocytes treated with H 2 O 2 could induce bone marrow-derived MSCs to undergo apoptosis in vitro. In corollary in vivo experiments, Ras-Related Protein Rab27a-knockout mice were engineered to have reduced exosome release from cardiac tissues.…”
Section: Understanding the Paracrine Effects Exerted By Exosomes Secrmentioning
confidence: 99%
See 2 more Smart Citations